Intracranial Hypotension with Multiple Complications: An Unusual Case Report - Swetha Ade; Majaz Moonis (Case Reports in Neurological Medicine)
Background. Undiagnosed intracranial hypotension can result in several complications including subdural hematoma (SDH), subarachnoid hemorrhage (SAH), dural venous sinuses thrombosis (CVT), cranial nerve palsies, and stupor resulting from sagging of the brain. It is rare to see all the complications in one patient. Furthermore, imaging of the brain vasculature may reveal incidental asymptomatic small aneurysms. Given the combination of these imaging findings and a severe headache, the patients are often confused to have a primary subarachnoid hemorrhage. Case Report. We present a patient with spontaneous intracranial hypotension (SIH) who had an incidental ophthalmic artery aneurysm on MR imaging, and this presentation led to coiling of the aneurysm. The key aspect in the history “postural headaches” was missed, and this led to life threatening complications and unnecessary interventions. Revisiting the history and significant improvement in symptoms following an epidural blood patch resulted in the diagnosis of SIH. Conclusion. We strongly emphasize that appropriate history taking is the key in the diagnosis of SIH and providing timely treatment with an epidural blood patch could prevent potentially life threatening complications.